Harmonization of Islamic and Conventional Banking Law in Dual Banking System (Digital Transformation and Progressive Innovation) - Sari, Ayu Puspita (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
This study examines the harmonization of Islamic and conventional economic law within dual banking systems through progressive innovation and digital transformation. The research employs a normative legal approach combined with comparative analysis to investigate how dual banking systems can effectively integrate Islamic principles with conventional banking practices while maintaining regulatory coherence. The study reveals that successful harmonization requires comprehensive legal frameworks that accommodate both systems' distinct characteristics while leveraging digital technologies to enhance operational efficiency and regulatory compliance. Key findings indicate that progressive innovation in financial technology, coupled with adaptive regulatory frameworks, can facilitate seamless integration between Islamic and conventional banking operations. The research contributes to the understanding of how dual banking systems can evolve to meet contemporary financial demands while preserving the integrity of Islamic principles and conventional banking practices.Maximum 500 characters (with spaces)